Impact of Integrated Farming Systems on Socio- Economic Status of Farmers - Rathod, M K; Raut, Sonali (Journal of Agricultural Extension Management, 2019)
The present study was conducted in Wardha district of Vidarbha region inMaharashtra to study the impact of integrated farming system on socioeconomicstatus of farm families. The farmers who had adopted differentfarming systems in addition to agriculture were purposively selected from 12villages and personally interviewed. Data was collected regarding the impactof farming systems on socio-economic status of farmers, before and afteradoption of the farming system. Almost all indicators of SES were foundincreased in their levels after adoption of the fanning system. The resultsrevealed that overall socio-economic status improved after adoption ofintegrated farming system.